Graphical Genotype of KDML105xIR64 Backcross Lines Exhibited Rice Blast Resistance - Peangrawee Tongnun (Science Faculty of Chiang Mai University, 2019)
The rice blast resistance is an important characteristic to ensure stability in rice production. It protects the plant from the infection of rice blast fungus (Magnaporthe oryzae), the major concerned pathogen in every rice-growing country. In this study, graphical genotypes of 3 selected BC2F7 lines with blast resistant phenotype, derived from IR64 genome on the background genome of Thai jasmine rice, KDML105, were constructed. A total of 110 DNA markers (97 SSR and 13 InDel markers) were used to characterize the genetic makeup of the selected BC2F7 lines. The graphical genotype of the 3 selected backcross lines revealed that the majority of genetic background in backcross lines derived from KDML105 and small segments from IR64. These small genetic differences in backcross lines can result in large differences in rice blast resistant spectrum. Regions on chromosomes linked to molecular markers appear to be important loci governing blast resistance are as follows - Pi-kd/Pi-b on chromosome 2 at RM208, Pi-27(t) and Pi-zt on chromosome 6, and R-QTL on chromosome 9. In conclusion, the information obtained from our study indicating that this set of BC2F7 could be used as the donor in rice blast resistance breeding program.